Effects of the International Judo Federation Refereeing Rules on competition contents in the All-Japan Judo Championships: From the viewpoint of dynamic judo - Miyake, K.; Matsui, T.; Sato, T.; Yokoyama, T.; Takezawa, T.; Kawabata, K.; Akimoto, H. (Research Journal of Budo, 2015)
The All-Japan Judo Championships (AJJC) is an open-weight tournament for determining the best judoka in Japan. The AJJC has been held under the Kodokan Judo Refereeing Rules (KDK Rules) since 1951. In 2011, the All-Japan Judo Federation (AJJF) introduced the International Judo Federation Refereeing Rules (IJF Rules), which were formulated to facilitate more dynamic judo (increased wins by ippon, decreased wins by judges` decisions, and decreased mate-time). Although the IJF Rules has facilitated dynamic judo in international competitions, their effects on the competition contents in the AJJC are still unknown. Here, we aimed to clarify whether the introduction of the IJF Rules facilitated dynamic judo in the AJJC. The 221 judo matches in the AJJC from 2008 to 2013 were separated into two groups, the tournaments following the KDK Rules (2008-2010) and those following the IJF Rules (2011-2013). Their data were extracted from the AJJC records by Judo, the official Kodokan journal, and from the match videos recorded by the AJJF. We analyzed the proportions of winning contents (wins by ippon or superior performance), winning methods (points from techniques or penalties, or judges` decisions), techniques for getting points (te-waza, koshi-waza, ashi-waza, sutemi-waza, or katame-waza) and the mate-time for each match. A chi-square test and an independent t-test were used to perform statistical analyses, and for each test, statistical significance was assumed at P value < 0.05. For the winning methods of the IJF Rules` and the KDK Rules` tournaments, the proportion of points from techniques (60.4% vs. 53.6%) and points from penalties (23.4% vs. 15.5%) showed no differences, but the proportion of wins by judges` decisions in the IJF Rules` tournaments was significantly lower than in the KDK Rules` tournaments (16.2% vs. 30.9%) (P < 0.05). Furthermore, the mate-time in the IJF Rules` tournaments was significantly shorter than in the KDK Rules` tournaments (77 s vs. 105 s) (P < 0.01). However, the winning contents and techniques for obtaining points showed no differences between the IJF Rules` and the KDK Rules` tournaments. We confirmed for the first time that the IJF Rules did not affect the winning contents and techniques for getting points, but decreased the proportion of judges` decisions and mate-time in the AJJC. These findings suggest that the IJF Rules partially facilitated dynamic judo in the AJJC.